GEOTEC (Geothermal-Enhanced Ocean Thermal Energy Conversion) engineering concept study (TRW Energy Development Group, Redondo Beach, CA (USA), 1984)
The project was to provide a conceptual design for a modular state-of-the-art geothermal-enhanced ocean thermal energy conversion (GEOTEC) plant for implementation at a Navy site on Adak Island, Alaska. This report includes the following appendices: (1) statement of work; (2) geothermal resource assessment; (3) assessment of environmental issues; (4) design optimization program formulations for GEOTEC; (5) calculation of geofluid temperature drop in brine collection system; (6) pressure losses and pumping requirements for seawater pipeline system; (7) geocost comparison of single and dual binary cycle systems; (8) description of seawater pipeline system; and (9) plant system installed cost estimates. (ACR)